Analisa Produktivitas Excavator di Area PIT 2 Swakelola Tambang Banko Barat PT Bukit Asam, Tbk - Ghony, Muhammad Abdul; Aristo; Sarmidi (Fakultas Teknik UMRI, 2023)
A good coal mining process is assessed by productivity and efficiency. Productivity can also be increased by using heavy equipment accompanied by competent operators. As one of the largest coal mining companies in Indonesia, PT Bukit Asam, Tbk is required to always be at the best performance, including at the heavy equipment operator level. This research aims to determine the factors of heavy equipment use as assessed by cycle time on coal productivity. Productivity is limited to the overburden loading process by the Komatsu PC3000SE excavator at PIT 2 Swakelola Tambang Banko Barat. The greatest productivity obtained was 1099 m3 per hour and the average percent productivity was 79.4%. In this research, a match factor of 0.8 was also obtained as a basis for further research that needs to be carried out to optimize the overburden loading and dumping process for PT Bukit Asam